2018
DOI: 10.5433/1679-0359.2018v39n4p1617
|View full text |Cite
|
Sign up to set email alerts
|

Marandu palisade grass management strategies at the beginning of the deferment period and effects on tillering

Abstract: Pasture mowing at the beginning of deferment stimulates tillering and can be used in different ways. The aim of this study was to understand how the mowing of Urochloa brizantha cv. Marandu Syn. Brachiaria brizantha cv. Marandu (marandu palisade grass) prior to the deferment period modifies tillering activity and the characteristics of young, mature, and old tillers. Three mowing strategies were evaluated: canopies kept at a height of 15 cm for five months before deferment (15/15 cm); canopies kept at 30 cm (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…Possibly, the young tillers that emerged in the early spring were developed during the grazing period, becoming older, especially in the short/mown pastures during late winter. The old tiller shows a worse morphological composition than the young tiller, which is conformity with the results of Santos et al (2018). These authors observed that the weight and percentage of live stems from old tillers were bigger in relation to young tillers; the percentage of live leaf lamina was bigger in young tiller (52.6%) and lower in old tiller (21.3%); and the percentage of dead leaf lamina was bigger in the old than in young tillers.…”
Section: Discussionsupporting
confidence: 85%
“…Possibly, the young tillers that emerged in the early spring were developed during the grazing period, becoming older, especially in the short/mown pastures during late winter. The old tiller shows a worse morphological composition than the young tiller, which is conformity with the results of Santos et al (2018). These authors observed that the weight and percentage of live stems from old tillers were bigger in relation to young tillers; the percentage of live leaf lamina was bigger in young tiller (52.6%) and lower in old tiller (21.3%); and the percentage of dead leaf lamina was bigger in the old than in young tillers.…”
Section: Discussionsupporting
confidence: 85%
“…It is noteworthy that the structural characteristics of old tillers are generally worse compared to those of young and mature tillers, as observed by Barbosa et al (2012) with guinea grass cv. Tanzania and Santos et al (2018) with marandu palisadegrass.…”
Section: Discussionmentioning
confidence: 99%
“…Variations of appearance and mortality of tillers during spring and summer, caused by the structure of late winter grasses, can alter the relative participation of tillers of different ages in the pasture. This has relevant consequences because young tillers have greater growth rates (MONTAGNER et al, 2011;BARBOSA et al, 2012), better structural characteristics (SANTOS et al, 2018) and nutritional value (SANTOS et al, 2006) and also, are more responsive to growth factors (PAIVA et al, 2011), when compared to old tillers.…”
Section: Introductionmentioning
confidence: 99%
“…The patterns of emergence and survival of tillers result in variations in the percentage of young, mature and old tillers in the pasture (M. E. R. Santos et al, 2018;Alves et al, 2019; M. E. R. Santos et al, 2020;A. N. D. Carvalho et al, 2019).…”
Section: Introductionmentioning
confidence: 99%